CURRENT KNOWLEDGE ABOUT THE ETIOPATHOGENESIS AND THERAPY OPTIONS FOR COVID-19 - Pesic, Srdjan; Jovanovic, Hristina; Trajkovic, Hristina (HEALTH CARE, 2020)
Currently, over 35 million people in the world are infected with the COVID-19 and over a millionhave died. The pandemic character of the disease has imposed dynamic research both in the field ofclarification of the etiopathogenetic mechanisms of the disease and in the field of possible therapy.The amount of scientific knowledge has increased dozens of times in the last nine months, but we arestill not even close to define an effective and safe therapy. The knowledge that COVID-19 is not only arespiratory but also a multisystem disease, which affects almost all organs, gave us opportunities fortherapeutic adjustments. Strong oxidative stress, silent chronic hypoxia, increased coagulability, andincreased platelet aggregation are just some of the mechanisms in the development of the disease.Cardiovascular consequences and vascular endothelial dysfunction are thought to be mainly responsiblefor death with a dangerous cytokine storm and acute respiratory distress syndrome. Having all thisin mind in the therapeutic sense, it is proposed to use antibiotics, high doses of vitamin C, bloodtransfusion, immunoglobulin, interferon, anti-IL-6 antibodies, small doses of dexamethasone or othercorticosteroids, specific antiviral drugs such as favipiravir and remdesivir. The use of chloroquine isexcluded from the therapeutic protocols of the World Health Organization and the Centers for DiseaseControl and Prevention (United States of America). For preventive and supportive purposes, high dosesof vitamin D, vitamin C, zinc, probiotics, alpha-lipoic acid, and other supplements are recommended.The use of anti-inflammatory, analgo-antipyretics drugs is considered justified, as well as the use ofsmall doses of acetylsalicylic acid. Over 70 other drugs are currently being tested in over 400 clinicalstudies. In patients who already use corticosteroids by inhalation or intranasally due to asthma,chronic obstructive pulmonary disease, allergic rhinitis, or biological drugs due to immunomodulatoryinflammatory diseases, this therapy should not be changed and it is not a prerequisite condition formore severe forms of the disease. The specifics of the infection in special populations such as childrenor pregnant women must also be taken into consideration.
Keywords: COVID-19, etiopathogenesis, therapy